Preparation, characterisation, and application of plant protein-dairy protein hybrid nano assemblies : a thesis presented in partial fulfilment of the requirements for the degree of Master of Food Technology, Massey University, Auckland, New Zealand - Thind, Imaan (Massey University, 2026)
For centuries, pulses have played a significant role in human nutrition due to their high protein, dietary fibre, vitamins and minerals content. Faba bean is a good source of protein with a well-balanced amino acid profile and offers environmental advantages such as nitrogen fixation and adaptability to colder climates. Despite being rich in nutrients, faba bean proteins exhibit poor functionality, including low solubility, a high tendency to form aggregates, and the presence of antinutritional factors. These challenges limit the commercial use of faba bean proteins in food systems that require strong emulsification and gelation. Combining faba bean proteins with the dairy proteins is a promising approach to improve the functionality of faba bean protein isolate (FPI) while maintaining sustainability. This research is based on this background, which investigates how faba bean protein isolate (FPI) and whey protein isolate (WPI) can be combined to create a functional hybrid which addresses the growing sustainable needs. WPI is well known for its excellent functional properties, such as solubility, interfacial behaviour, and gelation, but it is not particularly sustainable. Combining FPI and WPI is a promising approach, but understanding their different behaviours and the best way to incorporate them is essential for practical use in food systems. In this study, FPI, WPI, and their blends were processed using heat treatment, cold sonication, and thermosonication to investigate the effects of these treatments on particle size, structural organisation, zeta potential, emulsification, and gelation properties. The untreated sample, especially those with high FPI content such as WPI: FPI (2:8 and 0:10), showed larger particle sizes due to stronger hydrophobic interactions. Cold sonication disrupted intermolecular bonds, resulting in a smaller particle size. In contrast, heat treatment was most effective on higher WPI-ratio mixtures (WPI: FPI (10:0 and 8:2)) rather than higher FPI-ratio mixtures (WPI: FPI (2:8 and 0:10)), resulting in higher turbidity and aggregation. Thermosonication was effective in producing smaller, more uniform particles across all samples. Zeta potential results showed that WPI-rich solutions (WPI: FPI (10:0 and 8:2)) exhibited higher negative charge and greater stability. SDS-PAGE confirmed structural changes in mixtures of different WPI: FPI ratios. The results showed that samples with higher FPI (WPI: FPI (2:8 and 0:10)) exhibited greater protein aggregation, particularly under non-reducing conditions. Among all the treatments, thermosonication showed the most precise and most organised band patterns, thus justifying the fact that it induces the reorganisation and unfolding of proteins more than any other treatment. Thermosonication significantly improved (P<0.05) emulsifying properties, especially of the higher FPI-ratio blends (WPI: FPI (2:8 and 0:10)). Under oscillatory rheology, these emulsions showed smaller oil droplet sizes and a stronger gel-like structure. Cold-sonication showed less improvement in emulsion stability and gel-like behaviour than thermosonication, and heat treatment was more effective on the blends with the higher WPI ratio, especially WPI: FPI (10:0). Overall, thermosonication enhanced interfacial behaviour, improved adsorption, and led to the formation of a stronger interfacial film. Acid-induced gels were formed using glucono-δ-lactone to study the gelation properties of the proteins. Untreated and cold-sonicated gels were weaker, while heat-treated gels were stronger, especially in higher WPI-ratio systems, particularly WPI: FPI (10:0). Among the treated gel samples across the WPI: FPI ratios studied, thermosonicated gels were the strongest as confirmed by confocal microscopy, which revealed uniform, dense structures. Water-holding capacity results further confirmed that the thermosonicated gels retained water better, even in higher FPI-ratio samples (WPI: FPI (5:5 and 0:10)). This can be explained by the combined effect of thermosonication's mechanical disruption and protein unfolding. These findings demonstrate that thermosonication, as a processing method, can help overcome the limitations of the FPI by forming a hybrid system with the WPI. The study shows that hybrids of these two proteins behave differently from the individual proteins, and this behaviour can be altered by using the proper processing method. Thermosonication produced the best and most consistent overall results by reducing particle size, improving emulsifying and gelation behaviour, and increasing water-holding capacity. This study highlights the potential of combining WPI and FPI to form hybrid systems that yield high-performing food formulations and support sustainability. This research provides the pathway to develop new protein formulations for the future of sustainable food production.
Figure 7A is reproduced with permission.
Keywords: 300607 Food technology